Volatile Aromatic Composition and Antimicrobial Activity of Different Types of Honey - Burgut, Aykut (Progress in Nutrition, 2020)
Total phenol contents and volatile aromatic compounds of five types of honey (pine, french lavender, chestnuts, thyme and milk vetch) were determined by Folin–Ciocalteau and GC-MS method, respectively. The honey samples were diluted in various concentrations (0%, 25%, 50%, 75% and 100%) and subjected to antimicrobial activity against eight common food-borne pathogens (Enterococus faecalis ATCC29212, Staphylococcus aureus ATCC29213, Klebsiella pneumoniae ATCC700603, Camplylobacter jejuni ATCC 33560, Listeria monocytogenes ATCC7677, Aeromonas hydrophila NCIMB 1135, Salmonella Parathypi A NCTC13 and Yersinia enterocolitica NCTC 11175). Total phenol contents of honeys were above 13.51 mg GA/g. A total of 64 compounds were identified, including 27 in French lavender honey, 19 in pine and thyme honey, 17 in chestnuts honey and 12 in milk vetch honey. From among the 64 identified constituents, only octane, trans-linalool oxide and cis-linalool oxide were found in all analysed samples. γ-decalactone were also present in all honey samples apart from French lavender chestnuts honey.  Chestnuts, pine and milk vetch honey seemed to have best antimicrobial activity against bacteria. The strongest inhibition effect of honey was observed on L. monocytogenes (>12 mm) and S. aureus (>4 mm). S. Paratyphi A and Y. enterocolitica were inhibited only by milk vetch honey (8.33 mm) and thyme honey (2.83 mm) at doses of 75%, respectively. The inhibition of C. jejuni was solely observed by undiluted pine and chestnuts honey. The study result emphasized the potential importance and use of chestnuts, pine and milk vetch honey due to their antimicrobial activity and chemical composition as food.